2010
DOI: 10.1167/iovs.09-3987
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amyloid Fibrils In Vitro from Partially Unfolded Intermediates of Human γC-Crystallin

Abstract: HgammaC-Crys formed amyloid fibrils on incubation at low pH via a partially unfolded intermediate. This process could contribute to the early stages of the formation of light-scattering species in the eye lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…Furthermore, it has been reported that amyloid fibril assembly occurs via unfolded or partially folded intermediates, containing large portions of PPII and random coil domains (Booth et al, 1997;Wang et al, 2010). Interestingly, our recent cryoEM studies demonstrated that amelogenin assembly occurs in a stepwise hierarchical process via oligomeric intermediates (Fang et al, 2011a,b).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, it has been reported that amyloid fibril assembly occurs via unfolded or partially folded intermediates, containing large portions of PPII and random coil domains (Booth et al, 1997;Wang et al, 2010). Interestingly, our recent cryoEM studies demonstrated that amelogenin assembly occurs in a stepwise hierarchical process via oligomeric intermediates (Fang et al, 2011a,b).…”
Section: Discussionmentioning
confidence: 94%
“…UVRR has been employed previously to characterize the core structure in Aβ(1-40) fibrils [56], as well as the fibrillization of other amyloidogenic peptides and proteins [57][58][59][60][61]. The UVRR spectrum of LMW Aβ(1-42) is visually similar to other disordered homo-polypeptides (Fig.…”
Section: Aβ(1-42)mentioning
confidence: 85%
“…It is worth noting that mutations in some of the crystallin genes have been associated with non-cataract abnormities such as neurodegenerative diseases, cardiomyopathy, tumorigenesis and retinal and vascular disorders [23][24][25][26]. Similar to proteins involved in neurodegenerative diseases, crystallins can also form amyloidlike fibrils under certain solution conditions [27][28][29][30][31][32][33]. However, the consequence of crystallin fibrillization in cataract formation, as well as in non-lens disorders, remains elusive since amorphous aggregates but not amyloid fibrils dominate the water-insoluble protein fractions isolated from cataractous lenses [3].…”
Section: Introductionmentioning
confidence: 99%